European perspectives on global imbalances - Alan Ahearne; Jürgen von Hagen (Bruegel, 2006)
The large and growing US current account deficit has its counterpart in the large and growing current account surpluses in Asia and in the major oil-exporting countries. Although Europe is not part of the problem of global imbalances, Europeans are concerned that a disproportionately large burden of adjustment will fall on Europe. Without more exchange rate flexibility in Asia, adjustment may involve excessive appreciation of European currencies. The euro-area economy is not flexible enough to cope easily with a substantial euro appreciation, which would depress already sluggish growth and exacerbate divergences within the euro area. If EU institutions do not deliver in the face of a sharp appreciation in the euro, Europe's responses could be more erratic, and there would be a greater risk of a more protectionist response.
Keywords: 330; Außenwirtschaftliches Gleichgewicht; USA; OPEC-Staaten; EU-Staaten